The Systematic Literature Review: Public Policy Implementation in Achieving Ecotourism Sustainability at Harau Valley Waterfall, West Sumatra - Batubara, Fanny Yuliana; Frinaldi, Aldri; Lanin, Dasman; Rembrandt, Rembrandt; Umar, Genius; Syah, Nurhasan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The Harau Valley Nature Tourism Park (TWA) faces complex sustainability challenges, with an increase in tourist visits reaching 270,790 visitors in 2022. This has led to ecological pressure, multi-stakeholder conflicts, and ambiguity regarding the destination's identity between conservation and commercial functions. This Systematic Literature Review (SLR) analyzes the multidimensional sustainability status (ecological, socio-cultural, economic, infrastructure), identifies gaps between formal public policy frameworks and field implementation practices, and formulates evidence-based, integrative policy recommendations. The study analyzes five peer-reviewed articles (2017-2024) using a multidimensional framework with MDS (Multidimensional Scaling), TALC (Tourist Area Life Cycle), and GRADE evidence synthesis. Inclusion criteria: publications in Indonesian/English, quantitative/qualitative/mixed-methods methodologies, field-based empirical research. The multidimensional sustainability index reached 59.45 (moderately sustainable) with dimension heterogeneity: ecology 66.52, infrastructure 65.66, economy 54.14, socio-culture 51.48. The optimal carrying capacity is 315,169 people/year, but temporal distribution is uneven, creating seasonal pressure. A significant gap was identified between formal regulations (Ministerial Decree, Regional Regulation) and implementation practices. The local leadership model of Tungku Tigo Sajarangan offers potential conflict resolution mechanisms for stakeholders. The Harau Valley Nature Tourism Park requires an integrative policy framework that balances conservation objectives, local livelihoods, and visitor satisfaction through community-centered governance, evidence-based quota systems, and the revitalization of traditional local leadership. A phased implementation is recommended, focusing on critical infrastructure (0-1 year), governance restructuring (1-3 years), and long-term ecological conservation (3-5 years).